Growing with Language: Innovation in Developing Indonesian Language Learning Materials - Triscova, Valentina; Sudaryono, Sudaryono; Ekawarna, Ekawarna (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This article is based on the developmental Development of Instructional Materials for Learning Indonesian Elementary School 4th. A model development is adapted from The development research aims to (1) Produce a learning teaching materials Indonesian grade 4 elementary school being used as a handle students and teachers. (2) Determine the effectiveness, efficient. The present model has been validated by some experts such as design and educational material expect. It also has been tested to the student at Elementary School Grade 4 semesters Jambi city. The resuls revealed that the product learning material is quite applicable to improve students knowledge in Learning Indonesian subject. The novelty of this research is that it creates a new approach to improving language skills through dynamic learning resources, adapted to the continuously developing needs of Indonesian language learners. In addition, with innovative strategies and the latest methodology, this research changes the paradigm of Indonesian language education by creating learning materials that are revolutionary, able to adapt and grow as learners develop, thereby fostering better language proficiency and cultural engagement.